Appearance of special colors in deuteranomalous trichromacy. (August 2021) - Lindsey, Delwin T.; Brown, Angela M.; Hutchinson, Lindsey N.
Abstract: Deuteranomalous color matching behavior is different from normal because the middle-wavelength sensitive cones contain an abnormal Lʹ pigment instead of the M pigment of the normal observer. However, there is growing evidence that deuteranomalous color experience is not very different from that of normal trichromats. Here, normal and deuteranomalous observers chose monochromatic unique yellow lights. They also chose broadband lights, displayed on a computer monitor, that corresponded to eight special colors: the Hering unique hues (red, yellow, green, blue), and binary colors perceptually midway between them (orange, lime, cyan, purple). Deuteranomalous monochromatic unique yellow was shifted towards red, but all the broadband special color selections were physically similar for normal and deuteranomalous observers. Deuteranomalous special colors, including monochromatic unique yellow, were similar to those of normal observers when expressed in a color-opponent chromaticity diagram based on their own visual pigments, but only if (1) color-opponent responses were normalized to white, and (2) the deuteranomalous diagram was expanded along the r – g dimension to compensate for the reduced difference between deuteranomalous L- and Lʹ-cone photopigments. Particularly, deuteranomalous observers did not choose binary colors with extra r – g impact to overcome their insensitivity along the r – g dimension. This result can only be compatible with the known abnormality of the deuteranomalous Lʹ photopigment if deuteranomalous observers adjust their perceptual representation of colors to compensate for their color vision deficiency.